Code Mixing in Cross-Cultural Communication of Junior High School Students of Al Kautsar - Syarifah Siregar; Sumarsih Sumarsih (Universitas Negeri Medan, 2016)
This study investigated code mixing in cross-cultural communication of Junior High School students of Al Kautsar. The objectives of the study namely: 1) To identify types of code-mixing that used in cross-cultural communication. 2) To find out the function of code-mixing used in cross-cultural communication. 3) To identify types of socio-cultural meaning that used in cross-cultural communication.4) To elaborate the main reasons of code-mixing used in cross-cultural communication. This research was conducted by descriptive qualitative research. The participants were 10 students in different ethnic. The data were students’ utterances in different ethnic that have taken from school environment. The findings showed that several types of code mixing, i.e. word insertion, phrase insertion, clause insertion, and tag mixing occured in cross-cultural communication. Word insertion is dominantly mixed by the students in daily conversation. The function of code mixing in cross-cultural communication namely as; 1) communication strategy, 2) expression personality or community, 3) style. And there were some types of socio-cultural meaning in cross-cultural communication, they are:1) a unique group solidarity, 2) a special register, 3) self esteem. And the main reasons of using code mixing in cross-cultural communication were: 1) being emphatic something (express solidarity. 2) interjection. 3) expressing group identity 4) and to soften or strengthen request or command. Keywords: code mixing, cross cultural communication, junior high school